Influence of the Choice of Transplant Material for Stabilization of the Cervical Spine on The Reduction of Stay in Hospital - Mamadaliyev Abbosbek Bakhtiyarovich; Eranov Sherzod Nuraliyevich; Tokhirova Zebuniso Shukhratjonovna (Scholars Digest Publishing, 2023)
We conducted a particular study, the aim of which was to determine the optimal method of surgical stabilization of the cervical spine in trauma and degenerative diseases. In determining the choice of method, we were guided not only the reliability and availability of the method, but also for early activation of patients in the postoperative period.
Keywords: biocompatibility, implants, cervical instability, cervical stabilization, anterior stabilization, average length of hospital stay.